The praxis of digital literacy in the EFL classroom: Digital-immigrant vs digital-native teacher - Kurniawati, Nia; Maolida, Elis Homsini; Anjaniputra, Agung Ginanjar (Universitas Pendidikan Indonesia, 2018)
Myriads of theories account for the primacy of digital literacy on ELT as the demand of the 21st century, yet studies on digital media literacy of distinct English teacher generations are thin on the ground. Thus, this descriptive qualitative study investigated the utilization of digital literacy in the EFL classroom of senior high school teachers from two generations (digital immigrant and digital native) and their students’ responses to the use of digital media in the English classroom in Indonesia. Three instruments were utilized including classroom observations, questionnaires, and interviews. Following ACOT’s (Apple Classroom of Tomorrow) framework, the findings show that both teachers were at the adaptation stage in terms of digital literacy and this was reflected on the utilization of digital media in assisting students’ learning. Yet, the digital-immigrant teacher appeared to be practically more adept in the implementation of digital media. As for the second issue, the students responded positively to the use of digital technology by the teachers to make English class more fun and comprehensible. However, when it comes to an ideal teacher, the students still considered good characters as the main criteria for an ideal teacher. Technology does support teachers in delivering the materials, but the way they behave and treat the students still also plays crucial part in maintaining a good relationship between teachers and students. The results show that the English teachers need to develop their digital literacy to keep up with the current demand to be professional English teachers in the digital era.